2022
DOI: 10.3390/en15041264
|View full text |Cite
|
Sign up to set email alerts
|

Energy-Based Approaches in Estimating Actual Evapotranspiration Focusing on Land Surface Temperature: A Review of Methods, Concepts, and Challenges

Abstract: The surface energy balance (SEB) model is a physically based approach in which aerodynamic principles and bulk transfer theory are used to estimate actual evapotranspiration. A wide range of different methods have been developed to parameterize the SEB equation; however, few studies addressed solutions to the SEB considering the land surface temperature (LST). Therefore, in the current review, a clear and comprehensive classification is provided for energy-based approaches considering the key role of LST in so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 294 publications
(390 reference statements)
1
2
0
Order By: Relevance
“…variability in stress levels and disease management across the field, aligning with prior studies by Benedetti and Rossini, (1993) and Thapa et al, (2019). Furthermore, the significance of NDVI in the pySEBAL model, particularly in delineating cold and hot pixels, has been highlighted by (Taheri et al 2022). This study underscores the utility of high resolution NDVI-based spatial analysis in elucidating temporal patterns of crop health and facilitating targeted interventions and management strategies for optimizing processing tomato production and precision water management.…”
Section: Normalized Difference Vegetation Index Spatial Variabilitysupporting
confidence: 70%
“…variability in stress levels and disease management across the field, aligning with prior studies by Benedetti and Rossini, (1993) and Thapa et al, (2019). Furthermore, the significance of NDVI in the pySEBAL model, particularly in delineating cold and hot pixels, has been highlighted by (Taheri et al 2022). This study underscores the utility of high resolution NDVI-based spatial analysis in elucidating temporal patterns of crop health and facilitating targeted interventions and management strategies for optimizing processing tomato production and precision water management.…”
Section: Normalized Difference Vegetation Index Spatial Variabilitysupporting
confidence: 70%
“…This finding was in line with previous studies that have indicated that ET was constrained by moisture in arid regions and that the surface energy fluxes were dominated by sensible heat fluxes. In contrast, in the humid subsurface, ET was mainly limited by energy supply, with smaller sensible heat fluxes, and the surface energy fluxes were dominated by latent heat transfer (Taheri et al, 2022). The elevated CO 2 concentration (Liu et al, 2021a), land use/land cover change (LULCC) (Sterling et al, 2013;Li et al, 2017), and reservoir storage (Scanlon et al, 2018) may also have larger impacts on ET by changing the local water and energy balance.…”
Section: Discussionmentioning
confidence: 99%
“…METRIC is similar to SEBAL but provides the possibility to consider surface slope and aspect, as outlined by [16]. SSEBop, a straightforward, cost-effective, and operational model, requires minimal computational resources and automatically selects reference pixels [121].…”
Section: Type Models Advantages Disadvantagesmentioning
confidence: 99%